2014
DOI: 10.1002/jps.23926
|View full text |Cite
|
Sign up to set email alerts
|

Protein Quantity on the Air–Solid Interface Determines Degradation Rates of Human Growth Hormone in Lyophilized Samples

Abstract: rhGH was lyophilized with various glass-forming stabilizers, employing cycles that incorporated various freezing and annealing procedures to manipulate glass formation kinetics, associated relaxation processes and glass specific surface areas (SSA’s). The secondary structure in the cake was monitored by IR and in reconstituted samples by CD. The rhGH concentrations on the surface of lyophilized powders were determined from ESCA. Tg, SSA’s and water contents were determined immediately after lyophilization. Lyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 59 publications
(155 reference statements)
2
42
0
Order By: Relevance
“…13 After holding the samples at À45 C for 400 min, the shelf temperature was increased to À5 C during 30 min and held at À5 C for 6 h. Then the shelf temperature was reduced to À45 C at 1.3 C/min and held at this temperature for 6 h.…”
Section: Lyophilization Of Placebo and Protein-containing Formulationsmentioning
confidence: 99%
“…13 After holding the samples at À45 C for 400 min, the shelf temperature was increased to À5 C during 30 min and held at À5 C for 6 h. Then the shelf temperature was reduced to À45 C at 1.3 C/min and held at this temperature for 6 h.…”
Section: Lyophilization Of Placebo and Protein-containing Formulationsmentioning
confidence: 99%
“…Also, note that crystallization of a solute (such as buffer or lyoprotector) would be an additional source of a heterogeneity, solute crystallization and its relevance to stability of frozen and freeze-dried formulations was discussed elsewhere [5,10,11,64] and not considered here. Difference in the stability of different populations of proteins was convincingly demonstrated for the case of proteins on air-solid interface in freeze-dried cakes, [31] with the degradation rates on the interface exceeding the rate of bulk molecules by at least two orders of magnitude. As a result of such heterogeneity, shelf life of a pharmaceutical protein formulation would be limited by the most unstable population of protein molecules.…”
Section: Discussionmentioning
confidence: 93%
“…It was shown that concentration of albumin in dimethyl sulfoxide (DMSO)/water solutions was high at the ice interface at low temperatures and as much as 20 % of the albumin (for 32-53 mg/mL solutions) can be adsorbed on the ice or entrapped in the ice phase. In a recent study of the freezedried recombinant human growth hormone (rhGH) [31], the amount of protein on the surface of the freeze-dried cake was determined using electron spectroscopy for chemical analysis in formulations with sucrose, trehalose and hydroxyethyl starch (HES). The freeze-dried formulations were prepared at five different freezing conditions that include standard lyophilization cycle with slow freezing, pre-annealing before primary drying, post-annealing after secondary drying, fast freezing by immersion of vials into liquid nitrogen, and fast freezing of droplets by pipetting solution into immersed in liquid nitrogen vial.…”
Section: Experimental Evidences Of Heterogeneity Of Protein Environmementioning
confidence: 99%
“…9,12,[17][18][19] After sublimation of ice crystals during primary drying, these protein molecules would be found at the remaining glassy solid-air interface. 9,20,21 In 2 recent studies, the extent of damage (oxidation, deamidation, and aggregation) to 2 therapeutic proteins observed after long-term storage correlated directly with the amount of protein exposed on the glassy solid-air interface. 20,21 Annealing the frozen formulations prior to drying reduced the specific surface areas (SSAs) of the glassy solid and the fraction of protein exposed at the solid-air interface, which in turn significantly reduced degradation of the protein.…”
Section: Introductionmentioning
confidence: 98%
“…9,20,21 In 2 recent studies, the extent of damage (oxidation, deamidation, and aggregation) to 2 therapeutic proteins observed after long-term storage correlated directly with the amount of protein exposed on the glassy solid-air interface. 20,21 Annealing the frozen formulations prior to drying reduced the specific surface areas (SSAs) of the glassy solid and the fraction of protein exposed at the solid-air interface, which in turn significantly reduced degradation of the protein. 21 The first goal of this study was to test the hypothesis that conditions that result in lower amounts of a model antibody therapeutic on the surface of glassy solids would in turn reduce aggregation and particle formation rates during storage.…”
Section: Introductionmentioning
confidence: 98%